CYBER NOTARIAT DALAM SISTEM HUKUM INDONESIA: INOVASI, REGULASI, DAN TANTANGAN HUKUM - Ritonga, Abdullah Ahmad; Gultom, Josef Partogi; Ramayudi, Naufal (Faculty Of Law, Universitas Tanjungpura, 2025)
Abstract Cyber Notariat is an innovation in notarial practice in Indonesia that utilizes information technology for the creation, signing, and storage of authentic deeds electronically. This practice offers convenience, efficiency, and accessibility, particularly in the digital era and during the COVID-19 pandemic. However, its implementation raises legal challenges related to the certainty of deeds, data protection, electronic signature validity, and notary responsibility. Relevant regulations include Law No. 2 of 2014 on the Notary Position, Law No. 11 of 2008 and Law No. 19 of 2016 on Electronic Information and Transactions, and Law No. 27 of 2022 on Personal Data Protection. The Supreme Court has affirmed that electronic deeds created according to procedures have the same legal force as conventional deeds. To mitigate legal risks, notaries must comply with technical and legal standards, including digital authentication, data encryption, and audit trails, as well as provide public education. This study emphasizes that legal certainty and protection for parties using Cyber Notariat can only be achieved if regulations are consistently enforced and digital practices are strictly supervised. Abstrak Cyber Notariat merupakan inovasi dalam praktik notaris di Indonesia yang memanfaatkan teknologi informasi untuk pembuatan, penandatanganan, dan penyimpanan akta otentik secara elektronik. Praktik ini menawarkan kemudahan, efisiensi, dan aksesibilitas, terutama di era digital dan pandemi COVID-19. Namun, implementasinya menghadirkan tantangan hukum terkait kepastian akta, perlindungan data, validitas tanda tangan elektronik, dan tanggung jawab notaris. Regulasi yang relevan mencakup UU Nomor 2 Tahun 2014 tentang Jabatan Notaris, UU Nomor 11 Tahun 2008 jo. UU Nomor 19 Tahun 2016 jo. UU Nomor 1 Tahun 2024 tentang ITE, serta UU Nomor 27 Tahun 2022 tentang Perlindungan Data Pribadi. Mahkamah Agung melalui putusan-putusan terkait akta elektronik menegaskan bahwa akta elektronik yang dibuat sesuai prosedur memiliki kekuatan hukum sama dengan akta konvensional. Untuk meminimalkan risiko hukum, notaris harus mematuhi standar teknis dan prosedur hukum, termasuk autentikasi digital, enkripsi data, dan audit trail, serta melakukan edukasi kepada masyarakat. Studi ini menekankan bahwa kepastian hukum dan perlindungan pihak yang menggunakan Cyber Notariat hanya dapat terwujud apabila regulasi dijalankan secara konsisten dan praktik digital diawasi secara ketat.